2016
DOI: 10.18632/oncotarget.13137
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory loop involving miR-29c and Sp1 elevates the TGF-β1 mediated epithelial-to-mesenchymal transition in lung cancer

Abstract: Specificity protein1 (Sp1) is required for TGF-β-induced epithelial-to-mesenchymal transition (EMT) which has been demonstrated to aggravate the progression of cancer including lung cancer. microRNA-29c (miR-29c) is identified to inhibit EMT, but the correlation between miR-29c and Sp1 in human lung cancer remain incompletely clarified. Here, we confirmed decreased expression of miR-29c and enhanced expression of Sp1 in lung cancer tissues (n = 20) and found that Sp1 could be targeted and inhibited by miR-29c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 20 publications
(24 reference statements)
5
33
0
1
Order By: Relevance
“…SP1 is a nuclear transcription factor that plays an important regulatory role in mammalian gene expression. SP1 affects the growth and metastasis of tumors by regulating the expressions of tumor‐related genes . It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SP1 is a nuclear transcription factor that plays an important regulatory role in mammalian gene expression. SP1 affects the growth and metastasis of tumors by regulating the expressions of tumor‐related genes . It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors .…”
Section: Discussionmentioning
confidence: 99%
“…SP1 affects the growth and metastasis of tumors by regulating the expressions of tumor-related genes. [26][27][28] It can bind to specific sites on the promoter of vascular endothelial growth factor (VEGF) or VEGF receptor, which further promotes the progress of tumors. 29 SP1-regulated tumor-related genes are involved in a variety of cell functions, including cell cycle (Cyclin D1, TGF-α, E2F1), 30,31 apoptosis (Bax, Bcl2), 32,33 tumor metastasis (TGF-β, MMP2) 34 and angiogenesis (VEGF).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Zhang et al proposes a mechanism of action for miR-29c in non-small cell lung cancer. Their data suggests that miR-29c directly represses specificity protein1 (Sp1), a key protein involved in TGF-β-mediated epithelial-tomesenchymal transition (EMT) and cell invasion [34]. The theory that miR-125a functions as a tumor suppressor is supported by data from Tang et al, who transfected miR-125a mimics into human hepatocellular carcinoma (HCC) cell lines and demonstrated that colony formation and migration rates were decreased in miR-125a upregulated cells.…”
Section: Discussionmentioning
confidence: 98%
“…Han et al (11) identified that loss of miR-29c-3p expression was an early event in the initiation of gastric carcinogenesis. Other studies have revealed that miR-29c-3p was associated with lung cancer (12), nasopharyngeal carcinoma (13), acute myeloid leukemia (14) and breast cancer (15).…”
Section: Introductionmentioning
confidence: 97%